Effect of night fishing light on the orientation of sea turtle hatchlings - Muhamad Saini Suliansa (Universiti Pertanian Malaysia, 2012)
A study on sea orientation of newly emerged turtle hatchlings after exposure to two kinds of night fishing lights (fluorenscent lamps of squid jigging boats and light raft gas lamps purse seines) was carried out.